Return to Play After Hook of Hamate Excision in Baseball Players. Issue 10 (16th October 2018) - Burleson, Andrew; Shin, Steven
Background: Fractures of the hook of hamate in baseball players are significant injuries that can lead to pain and missed time from competition. The diagnosis is typically delayed because of the vagueness of symptoms and normal radiographic findings. Excision of the nonunited fragment has been supported as the primary treatment, but there are currently limited information and data on a timetable for return to competition after surgery. Purpose: To report on a large cohort of competitive baseball players with hook of hamate fractures treated with excision of the fragment and to assess the timetable for return to full athletic competition. Study Design: Case series; Level of evidence, 4. Methods: Competitive baseball players treated between 2012 and 2017 with hook of hamate excision for acute fractures or chronic fracture nonunions were retrospectively identified. All patients were treated by the same surgeon, and the time to return to full athletic competition was assessed. Return to play was defined as reaching the athlete's preinjury level and being able to perform full sport activities. Results: A total of 41 baseball players were identified, all of whom were documented to have a chronic presentation of a nonunion or partial union. The population consisted completely of male athletes, with a median age of 21 years (range, 18-34 years). All patients were competitive athletes, with 12 professional baseball players, 17 collegiate baseball players, and 12 high school baseball players. All patients were treated with hook of hamate excision, with 7 patients undergoing concomitant procedures as indicated. The median time to return to play was 5 weeks (range, 3-7 weeks). The time to return to play was similar between professional, collegiate, and high school athletes. All athletes returned to their preinjury level of activity by 7 weeks postoperatively. Conclusion: This study confirms that excision of the fractured hook provides predictable, early return to play, with a limited complication rate.